A novel chemical/biological combined technique for N, N-dimethylformamide wastewater treatment. Issue 9 (2nd May 2016) - Chen, Yingwen; Li, Bing; Qiu, Yu; Xu, Xiaoliang; Shen, Shubao
ABSTRACT: N, N-Dimethylformamide (DMF) is a widely used organic solvent whose wastewater is difficult to biodegrade directly. In this paper, a novel chemical/biological combined technique consisting of alkaline hydrolysis stripping, activated sludge and a bio-trickling filter (BTF) was developed for DMF wastewater treatment. The main pollutant, DMF, was decomposed to dimethylamine and formate under alkaline conditions, and the dimethylamine was stripped out by the BTF. The pretreated wastewater was then degraded in an activated sludge process. The operation performances of alkaline hydrolysis, activated sludge and BTF processes were investigated separately. At the optimal conditions of an alkali dosage of 40 g/L, an air/liquid ratio of 3000:1 and 5 h in the air-stripping process, the removal of total organic carbon and DMF was found to be 58% and 96%, respectively. A chemical oxygen demand removal efficiency of 80–90% was obtained in the activated sludge process. The performance of BTF was excellent with a dimethylamine removal efficiency close to 90% even at a high loading of 16 g/d.